Lettera a Casimir Ulrich Böhlendorff. Nürtingen presso Stoccarda, 4 dicembre 1801 (Studia theodisca, 2017)
Friedrich Hölderlin’s letter to his friend Casimir Ulrich Böhlendorff (December 4th 1801), a major biographical and poetological document for scholars, in the Italian translation by Gianni Bertocchini.